Revitalización del espacio público de la calle 13 entre carrera 20 carrera 24 del Municipio de Bucaramanga (2023)
The objective of this work was to propose an urban planning proposal for the public space located on 13th Street from 20th to 24th Streets, surrounding the San Francisco Market Square, in the city of Bucaramanga. In order to achieve a revitalization through the implementation of methodology with a transversal non-experimental design.